Three-dimensional coverage control for multi-unmanned aerial vehicle - Siow, Wen Hao (2024)
Multi-Agent Systems (MAS) facilitate complex systems by enabling self-governing agents to collaborate towards common goals. Within MAS, coverage control plays a vital role in optimizing agent deployment for area coverage. Hence, this research addresses the development and evaluation of a Three-Dimensional (3D) coverage control algorithm for Multi Unmanned Aerial Vehicle (MUAV). This project aims to model and simulate a group of quadrotors for area coverage in 3D space with the objectives of reviewing existing MUAV coverage methods, algorithm development, and assessing computational load, convergence, path length, coverage quality, and scalability in both Two-Dimensional (2D) and 3D spaces. The study begins with a literature review categorizing coverage problems into barrier, blanket, and sweeping coverage, alongside different coverage control strategies such as centralized, decentralized, and hybrid approaches. The transition from 2D to 3D algorithms is highlighted as a contemporary trend, as 2D coverage algorithms are sufficient for simple coverage tasks but lack the ability to handle complex coverage tasks. The Multi-step Broadcast Control (MBC) scheme emerges as a key reference due to its effectiveness in scalability and computational efficiency. This study proposes a 3D coverage control algorithm to address complex real-world scenarios, wherein the 3D control algorithm will be developed based on the 2D MBC scheme. The performance of the transitioned 3D algorithm is evaluated against the original 2D MBC algorithm in terms of computational load, convergence analysis, path length, coverage quality, and scalability. Results indicate that while the 3D algorithm exhibits higher computational load, it surpasses the 2D algorithm in convergence analysis and path length, maintaining consistent coverage quality and scalability. Objectives of this project are achieved by reviewing existing coverage control methods, developing, and evaluating the proposed 3D coverage control algorithm, demonstrating its effectiveness, and potential applicability in real-life scenarios.